Calcitriol inhibits migration and invasion of renal cell carcinoma cells by suppressing Smad2/3‐, STAT3‐ and β‐catenin‐mediated epithelial‐mesenchymal transition. Issue 1 (4th January 2020) - Xu, Shen; Zhang, Zhi‐Hui; Fu, Lin; Song, Jin; Xie, Dong‐Dong; Yu, De‐Xin; Xu, De‐Xiang; Sun, Guo‐Ping
Abstract: Low vitamin D status is associated with progression in patients with renal cell carcinoma (RCC). The present study found that vimentin, a mesenchymal marker, was accordingly upregulated, and E‐cadherin, an epithelial marker, was downregulated in RCC patients with low vitamin D status. Thus, we investigated the effects of calcitriol or vitamin D3, an active form of vitamin D, on epithelial‐mesenchymal transition (EMT) in RCC cells. RCC cells were treated by two models. In model 1, three RCC cell lines, ACHN, 786‐O and CAKI‐2, were incubated with either LPS (2.0 μg/mL) or transforming growth factor (TGF)‐β1 (10 ng/mL) in the presence or absence of calcitriol (200 nmol/L). In model 2, two RCC cell lines, ACHN and CAKI‐2, were incubated with calcitriol (200 nmol/L) only. Calcitriol inhibited migration and invasion not only in TGF‐β1‐stimulated but also in TGF‐β1‐unstimulated RCC cells. Moreover, calcitriol suppressed E‐cadherin downregulation and vimentin upregulation not only in TGF‐β1‐stimulated but also in TGF‐β1‐unstimulated ACHN and CAKI‐2 cells. Calcitriol attenuated LPS‐induced upregulation of MMP‐2, MMP‐7, MMP‐9, MMP‐26 and urokinase‐type plasminogen activator (u‐PA) in ACHN cells. In addition, calcitriol blocked TGF‐β1‐induced nuclear translocation of ZEB1, Snail and Twist1 in ACHN and CAKI‐2 cells. Mechanistically, calcitriol suppressed EMT through different signaling pathways: (i) calcitriol suppressed Smad2/3 phosphorylation by reinforcing physical interaction between vitamin D receptor (VDR) and Smad3 in TGF‐β1‐stimulated RCC cells; (ii) calcitriol inhibited signal transducer and activator of transcription (STAT)3 activation in LPS‐stimulated RCC cells; (iii) calcitriol inhibited β‐catenin/TCF‐4 activation by promoting integration of VDR with β‐catenin in TGF‐β1‐unstimulated RCC cells. Taken together, calcitriol inhibits migration and invasion of RCC cells partially by suppressing Smad2/3‐, STAT3‐ and β‐catenin‐mediated EMT. Abstract : Calcitriol suppressed EMT through two different signaling pathways: (i) calcitriol suppressed Smad2/3 phosphorylation by reinforcing physical interaction between vitamin D receptor (VDR) and Smad3 in TGF‐β1‐stimulated RCC cells; (ii) calcitriol inhibited β‐catenin/TCF‐4 activation by promoting integration of VDR with β‐catenin in TGF‐β1‐unstimulated RCC cells. Taken together, calcitriol inhibits migration and invasion of RCC cells by suppressing Smad2/3‐ and β‐catenin‐mediated EMT.